Peningkatan Kemampuan Berhitung Dengan Menggunakan Media Abakus Pada Siswa Kelas I SD 1 Melayu Kota Bima - Pravithasari, Ade (Universitas Nggusuwaru, 2023)
Low learning achievement, activeness, and student participation, especially in Mathematics subjects due to the limitations of teaching materials, media, and teaching methods are the background of this Research. This study aims to determine the improvement of students' numeracy skills through the Abaku method. This research was carried out at SD Negeri 1 Melayu Bima City. The subject of the study was grade I students consisting of 25 students. The object of the research is the learning achievement of students. The results of the study in Cycle I showed that the increase in students' numeracy skills achieved an average score of 64 with a completion percentage of 75%. In the second cycle, it achieved an average score of 86 with a completeness presentation of 96%. The conclusion that can be obtained is that the use of Abakus Media can improve Numeracy Skills in grade I students of SD Negeri 1 Melayu Bima City